ANALISIS SOAL HIGHER ORDER THINKING SKILL (HOTS) BUKU PAKET MATEMATIKA SEKOLAH MENENGAH KEJURUAN KELAS X - Neneng Nikmatul Zahro; Suryo Widodo; Yuni Katminingsih; Lilia Sinta Wahyuniar (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
Education in Indonesia currently still uses textbooks as teaching materials. On the other hand, students are required to have the ability to think critically, collaborate, communicate, and be creative. However, the textbooks used in schools today still have weaknesses, mainly mathematics textbooks. One of the weaknesses found is that there are only a small number of practice questions in the mathematics textbook, which can be grouped into HOTS questions. Based on this, this research was conducted to describe the distribution of HOTS-type questions in the 2017 revised edition of the Vocational High School (SMK) mathematics textbook for class X semester one published by the Ministry of Education and Culture of the Republic of Indonesia in the material Three-Variable Linear Equation System. The research was reviewed based on the definition of HOTS questions according to Brookhart (2014), namely analyzing, evaluating, creating, reasoning and logic, making decisions, solving problems, and thinking creatively. The approach used is a descriptive quantitative approach with the researcher's agreement technique using a formula. There are 20 questions used in this study. The results of this study are that 20 questions are said to include HOTS questions with the fulfillment of HOTS question indicators, according to Brookhart, and the results of the agreement of the two analysts.